2004
DOI: 10.1158/0008-5472.can-04-1231
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Delivery of Glucosylated Polyethylenimine/Phosphatase and Tensin Homologue Deleted on Chromosome 10 Complex Suppresses Akt Downstream Pathways in the Lung of K- ras Null Mice

Abstract: Difficulties in achieving long-term survival of lung cancer patients treated with conventional therapies suggest that novel approaches are required. Although several genes have been investigated for antitumor activities using gene delivery, problems surrounding the methods used such as efficiency, specificity, and toxicity hinder its application as an effective therapy. This has lead to the re-emergence of aerosol gene delivery as a noninvasive approach to lung cancer therapy. In this study, glucosylated conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 38 publications
8
39
0
Order By: Relevance
“…27 Our result showed that Akt/mTOR-mediated signals were significantly decreased by repeated delivery of PTEN in lungs of K-ras LA1 mice (Figures 3a and b). Kim et al 23 also reported that aerosol delivery of PTEN could suppress Akt activity, mTOR, and p70S6K protein expression in K-ras null mice. Our results, combined with other evidences, suggest that overexpressed PTEN-mediated suppression of Akt-related signals may also be responsible for tumor suppression in the lungs of K-ras LA1 lung cancer mouse model.…”
Section: Discussionmentioning
confidence: 96%
“…27 Our result showed that Akt/mTOR-mediated signals were significantly decreased by repeated delivery of PTEN in lungs of K-ras LA1 mice (Figures 3a and b). Kim et al 23 also reported that aerosol delivery of PTEN could suppress Akt activity, mTOR, and p70S6K protein expression in K-ras null mice. Our results, combined with other evidences, suggest that overexpressed PTEN-mediated suppression of Akt-related signals may also be responsible for tumor suppression in the lungs of K-ras LA1 lung cancer mouse model.…”
Section: Discussionmentioning
confidence: 96%
“…86-23, revised 1985). Mice were placed in nose-only exposure chamber (Dusturbo, Seoul, Korea) and exposed to the aerosol based on the method used previously (6). Briefly, aerosol was generated using the patented nebulizer (patent no.…”
Section: Methodsmentioning
confidence: 99%
“…However, the degree of toxicity (3) and the subject's immune response against such vectors upon repeated administration limited application of such systems in practice (4,5). Moreover, viral vectors are difficult to produce on a large scale (6). Nonviral vectors, on the other hand, have been increasingly proposed as safer alternatives to viral vectors for their potential to be given repeatedly with minimal host immune response.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) However, it is necessary for aerosols to be sprayed immediately because the stability of gene vectors in aqueous solution is low. 8) Alternatively, dry powder inhalers (DPIs) are widely used and accepted as an effective system for pulmonary drug delivery.…”
mentioning
confidence: 99%